2013
DOI: 10.1108/17542731311286432
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for sustainable improvement in technical education excellence

Abstract: Purpose -The purpose of this paper is to identify critical factors of total quality management (TQM), for use in a possible framework that addresses sustainable quality improvements in technical institutes as a plausible means of TQM implementation in higher education programs. Design/methodology/approach -The literature survey of the TQM and related quality methodologies and content analysis of TQM literature in technical institutes provide the theoretical and practical background for this work. The content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Responsibility with the TQM performance [27,[63][64][65] Support to improve the production process [51,66] Communication about the mission and objectives of the company [67][68][69] Quality policies and quality goals [70,71] Quality is the mean to increase profits [72,73] Dissemination of quality culture [74,75] Promotion of training and education [76,77] Training and education TQM courses to improve employee skills [78,79] TQM courses for managers and supervisors [79][80][81][82] Quality circle courses [79,81,83] Technical statistics courses [84][85][86] Financial resources for training [87][88][89][90][91] Courses on communication, effective meetings, and leadership [64,65,92] Courses on identification and troubleshooting [93][94][95] Employees integration…”
Section: Managerial Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Responsibility with the TQM performance [27,[63][64][65] Support to improve the production process [51,66] Communication about the mission and objectives of the company [67][68][69] Quality policies and quality goals [70,71] Quality is the mean to increase profits [72,73] Dissemination of quality culture [74,75] Promotion of training and education [76,77] Training and education TQM courses to improve employee skills [78,79] TQM courses for managers and supervisors [79][80][81][82] Quality circle courses [79,81,83] Technical statistics courses [84][85][86] Financial resources for training [87][88][89][90][91] Courses on communication, effective meetings, and leadership [64,65,92] Courses on identification and troubleshooting [93][94][95] Employees integration…”
Section: Managerial Commitmentmentioning
confidence: 99%
“…Promotion of continuous improvement [82,[103][104][105] Enhanced Production Processes [80,103,104] Cost reduction and its management [106][107][108] Higher productivity [109][110][111] Defect and waste disposal [23,51,104,109] Greater security for employees [23,51,109,112], [113] The final questionnaire is structured into three sections: demographic information, critical success factors of TQM, and benefits of TQM, which are answered on a Likert scale with values between one and five, where one indicates that this activity is not carried out or that the benefit is not obtained, and five indicates that the activity is always carried out or that the benefit is always obtained. This scale is used by Iqbal and Asrar-ul-Haq [23] to establish relationship between TQM practices and employee performance; and Singh, Kumar, and Singh, [33] to measure the impact of TQM on organizational performance in India.…”
Section: Managerial Commitmentmentioning
confidence: 99%
“…TQM advocates about the people development very explicitly because business excellence largely depends on the extent employees of an organization are capable in their respective fields. TQM uses employee capabilities in all activities and processes and makes collaboration feasible and real as comprehended [18,22]. It leads continuous improvement of the capabilities of the employees.…”
Section: Total Quality Management Implementationmentioning
confidence: 99%
“…In a TQM effort, all members of an organization participate in improving processes, products, services, and the culture in which they work. As specified by British Standard Institution, TQM is composed of a "management doctrine and company patterns which intent to rein the human and material resources of an organization in the most efficient way to attain the goal of the organization" [15,22].From these definitions, it is easily possible to identify the essential characteristics as well as the significant offerings of TQM, such as: continuous improvement; integration of people, functions and resources; systematic and structured approach; quality control at every level of the organization and at every step of the operating process; developing human and organizational capabilities; efficient utilization of resources; people participation; customer satisfaction; creating a quality culture and so on.…”
Section: Total Quality Management Implementationmentioning
confidence: 99%
“…Bobe and Kober (2015) found in an empirical study that effective management, coordinated research and networking are important for organisational success in the higher education. Sahu et al (2013) reported that the lack of research, poor infrastructure, non-commitment from senior management, lack of training and poor placements are the major issues for poor quality of technical education in India. Patil and Kamalpur (2012) explained that clear vision, management commitment, employee empowerment, continuous improvement and self-evaluation, teaching methodology and industry-institute interaction are the key quality factors which are important for organisational excellence.…”
Section: Factors Affecting Quality Of Technical Educationmentioning
confidence: 99%